Field Evaluation of Imidacloprid as an Insecticidal Seed Treatment of Cotton Cultivar with Particular References to Sucking Pest, Predator and Yield (Our Nature, 2013)
Imidacloprid is a neonicotinoid insecticide that has been used for controlling sucking pests of cotton. This study showed the efficacy of the imidacloprid insecticide, Gaucho 70 WS as seed dresser against aphids, whiteflies and thrips incidences on CB3 cotton cultivar. At the same time, inhabitants of the predators (ladybird beetles, lacewings, syrphids and spiders) and yield of the crop were evaluated. Fuzzy and delinted cotton seeds treated with imidacloprid reduced pest population compared to untreated control or foliar spray of monocrotophos 40 WSC at 1120 ml ha-1, and being the highest efficacy at 5.5 g kg-1 fuzzy seed. Cotton plants grown with imidacloprid treated seeds have abundances of ladybird beetles, lacewings, syrphids and spiders. The cotton cultivar produced significantly higher yield when seeds were treated with imidacloprid at 5.5 g kg-1 fuzzy seed. Therefore, use of imidacloprid, Gaucho 70 WS as a seed dresser may be an option for controlling sucking pests of cotton under field conditions.DOI: http://dx.doi.org/10.3126/on.v10i1.7750